2020
DOI: 10.1155/2020/8937657
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Erythropoietin Provides Protection against Renal Fibrosis in Adenine-Induced Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) causes anemia by renal damage. In CKD, the kidney is submitted to hypoxia, persistent inflammation, leading to fibrosis and permanent loss of renal function. Human recombinant erythropoietin (rEPO) has been widely used to treat CKD-associated anemia and is known to possess organ-protective properties that are independent from its well-established hematopoietic effects. Nonhematopoietic effects of EPO are mediated by an alternative receptor that is proposed to consist of a heterocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Adenine-induced nephropathy is a rat model of human tubulointerstitial fibrosis (TIF), which is the main pathological feature of various progressive renal damage and the final common pathway for chronic kidney disease (CKD). TIF is characterized by infiltration of renal interstitial monocytes and lymphocytes, myofibroblast activation, excessive deposition of extracellular matrix (ECM), and sclerosis [ 1 ]. Adenine is mainly used to participate in the synthesis of DNA and RNA and has been widely used for the treatment of patients with leukopenia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenine-induced nephropathy is a rat model of human tubulointerstitial fibrosis (TIF), which is the main pathological feature of various progressive renal damage and the final common pathway for chronic kidney disease (CKD). TIF is characterized by infiltration of renal interstitial monocytes and lymphocytes, myofibroblast activation, excessive deposition of extracellular matrix (ECM), and sclerosis [ 1 ]. Adenine is mainly used to participate in the synthesis of DNA and RNA and has been widely used for the treatment of patients with leukopenia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adenine produces 2,8-dihydroxyadenine through the action of xanthine oxidase, which deposits in the glomeruli and the interstitium, forming granulomatous inflammation and blocking the renal tubules leading to cystic dilatation of renal tubules and kidney failure [ 3 ]. Adenine-induced CKD rats exhibited anemia, uremia, decreased renal function, increased infiltration of inflammatory cells, tubular atrophy, and fibrosis [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that recombinant EPO provided renoprotection against fibrosis in adenine-induced CKD (48). However, EPO protected the IR kidney at the acute stage but promoted renal fibrosis in the long term.…”
Section: Epo and Its Derivativesmentioning
confidence: 94%
“…EPO exerts its hematopoietic properties through its connection with the homodimeric erythropoietin receptor (EPOR) on the precursors of the erythroid lineage in the bone marrow, accelerating the processes of erythropoiesis and increasing the number of mature erythrocytes (Watowich 2011, Kuhrt and Wojchowski 2015, Bhoopalan et al 2020. However, there is also a heterodimeric erythropoietin complex EPOR/ βCR, which consists of EPOR in combination with the ubiquitous β-common receptor (Brines et al 2004, Rivera-Cervantes et al 2019, Vázquez-Méndez et al 2020. Implementation of the cytoprotective properties of EPO in various models of ischemia-reperfusion is associated primarily with the activation of signaling cascades triggered by a short contact of erythropoietin with this receptor complex Cerami 2008, Collino et al 2015).…”
Section: Introductionmentioning
confidence: 99%